Evaluating the use of telemedicine in gynaecological practice: a systematic review. Issue 12 (7th December 2020) - Murugesu, Sughashini; Galazis, Nicolas; Jones, Benjamin P; Chan, Maxine; Bracewell-Milnes, Timothy; Ahmed-Salim, Yousra; Grewal, Karen; Timmerman, Dirk; Yazbek, Joseph; Bourne, Tom; Saso, Srdjan
Abstract : Objectives: The aim of this systematic review is to examine the use of telemedicine in the delivery and teaching of gynaecological clinical practice. To our knowledge, no other systematic review has assessed this broad topic. Design: Systematic review of all studies investigating the use of telemedicine in the provision of gynaecological care and education. The search for eligible studies followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and focused on three online databases: PubMed, Science Direct and SciFinder. Eligibility criteria: Only studies within gynaecology were considered for this review. Studies covering only obstetrics and with minimal information on gynaecology, or clinical medicine in general were excluded. All English language, peer-reviewed human studies were included. Relevant studies published up to the date of final submission of this review were considered with no restrictions to the publication year. Data extractions and synthesis: Data extracted included author details, year of publication and country of the study, study aim, sample size, methodology, sample characteristics, outcome measures and a summary of findings. Data extraction and qualitative assessment were performed by the first author and crossed checked by the second author. Quality assessment for each study was assessed using the Newcastle-Ottawa scale. Results: A literature search carried out in August 2020 yielded 313 records published between 1992 and 2018. Following a rigorous selection process, only 39 studies were included for this review published between 2000 and 2018. Of these, 19 assessed gynaecological clinical practice, eight assessed gynaecological education, one both, and 11 investigated the feasibility of telemedicine within gynaecological practice. 19 studies were classified as good, 12 fair and eight poor using the Newcastle-Ottawa scale. Telecolposcopy and abortion care were two areas where telemedicine was found to be effective in potentially speeding up diagnosis as well as providing patients with a wide range of management options. Studies focusing on education demonstrated that telementoring could improve teaching in a range of scenarios such as live surgery and international teleconferencing. Conclusions: The results of this review are promising and demonstrate that telemedicine has a role to play in improving clinical effectiveness and education within gynaecology. Its applications have been shown to be safe and effective in providing remote care and training. In the future, randomised controlled studies involving larger numbers of patients and operators with measurable outcomes are required in order to be able to draw reliable conclusions.